Administrative Ethics Conflict and Governance of Grassroots Government Staff Under the Human Relationship Society - Yin, Yue; Li, Taotao; Yang, Fan (Frontiers in Psychology, 2022)
The conflict of administrative morality among civil servants at the grassroots level arises from the background of China's long-standing traditional culture, and the current administrative system cannot keep up with the pace of economic development. In the process of grassroots management, due to the lag in the construction of administrative morality, the traditional official standard thinking, the imperfection of the current system, and the restriction of human nature, it is easy to cause the administrative moral conflict of the grassroots civil servants in practice. This paper takes the interpersonal society as the research background, analyzes the influence of the interpersonal society on the environment, and studies the administrative ethics conflicts and governance issues of basic civil servants from the interpersonal background. In addition, this paper conducts a more detailed field investigation based on fuzzy cluster analysis, analyzes the manifestations and causes of the administrative moral conflict of grassroots civil servants in the context of human society from multiple perspectives and levels, and then proposes countermeasures to solve the administrative moral conflict. The administrative moral conflict and governance of grass-roots civil servants under the background of interpersonal relationship is of great positive significance for solving the administrative moral conflict and improving the service awareness and service level of grass-roots civil servants.